CGIAR Excellence in Agronomy: Validating, tailoring, and expanding the cropping calendar agro-advisories in Ghana. Key Workshop Recommendations - Amankwah-Yeboah, Patricia; Ofosu-Ampong, Kingsley (2025)
Timely, accurate, and context-specific agro-advisories are essential for empowering smallholder farmers to make informed decisions throughout the agricultural season. In Ghana, while there is widespread knowledge on good agronomic practices (GAPs), significant challenges remain in translating this knowledge into accessible, actionable, and timely information, particularly for rural farmers dealing with increasingly variable climatic conditions. To address this gap, the Cropping Calendar Agro-Advisories tool was developed as a collaborative effort between the Council for Scientific and Industrial Research’s Institute for Scientific and Technological Information (CSIR-INSTI) and the Alliance of Bioversity International and CIAT, under the CGIAR Excellence in Agronomy (EiA) Initiative (now integrated into CGIAR’s Sustainable Farming Science Program). This innovative tool integrates multiple data sources and contextual factors to enhance the precision of agro-advisories . It brings together seasonal forecast data, soil and agronomic information, and crop phenology to align advisories with the crop growth stages. Additionally, it incorporates location-specific management recommendations tailored to local conditions, ensuring the advice is relevant, inclusive, and actionable for diverse user groups. The system is designed to deliver digital, location-specific advisories aligned with the physiological and management stages of key crops. The Validation Workshop, held on July 2, 2025, at the CSIR-Crops Research Institute (CRI), represented a critical step in the Cropping Calendar and Agro-Advisory System's development. The workshop’s goal was to refine and validate the advisory content to ensure its technical accuracy, contextual relevance, and usability for a broad range of end-users, including farmers, extension agents, digital service providers, and research institutions.